Assessing the Relative Influence of Individual Attitudes, Social Supports, and Neighborhood Context on Reentry Outcomes: What Changes Matter Most? - Alward, Lucas M. (Criminal justice and behavior, 2020)
Using the Serious and Violent Offender Reentry Initiative (SVORI) data set, the current study examined the relationship between internal change factors, including agency, readiness for change, and legal cynicism, and four reentry outcomes (recidivism, reincarceration, drug use, and treatment participation). The study also assessed the impact of external change factors, such as family support and perceived neighborhood quality on reentry outcomes. Using a hybrid model approach, we found that within-individual changes in agency and family emotional support were significantly related to decreased self-reported recidivism and reincarceration over time. Within-individual changes in family emotional support were also significantly related to reductions in self-reported drug use and within-individual changes in readiness for change were positively associated with treatment participation across the postrelease waves of the SVORI data. Between-individual results further demonstrate the salience of change factors on reentry outcomes. Study findings inform desistance models and identify some promising targets for reentry programming.